Diversity of Bird Communities in Tea (Camellia sinensis) Plantations in Fujian Province, South-Eastern China - Titus S. Imboma; Marco Ferrante; Min-sheng You; Shijun You; Gábor L. Lövei (Diversity, 2020)
Habitat conversion in mountain areas threatens their biodiversity. The effect on biodiversity of creating a mountain landscape with a network of forest fragments and a cultivated habitat matrix is poorly documented in China. Bird communities in forest fragments and tea plantations were censused by field observations in two years (2018–2019) in three tea-growing locations, Anxi, Beifeng, and Wuyishan in Fujian Province, south-eastern China. Out of a potential pool of 247 forest-associated bird species, we detected the presence of 82, mostly resident species, 32–47 of those regularly visiting tea plantations. Species-accumulation curves indicated the near-completeness of the census. The Rényi diversity profiles indicated a more diverse community in forest fragments than nearby tea plantations at Anxi and Beifeng, but the tea plantations at Wuyishan supported a more diverse bird community than the forest. Avian communities in tea plantations were a significantly nested subset of the forest communities. Tea plantations can provide resources for forest-associated birds, but the effectiveness of preserving avian diversity depends on natural forest fragments and can be enhanced by landscape-scale management, when the biocontrol potential of birds can also be enhanced.